Ta-Nehisi Coates and Roxanne Gay: Ethos or Alienation? - Radakovich, Micah Lynne (URJ-UCCS: Undergraduate Research Journal at UCCS, 2017)
This essay discusses the established ethos of Ta-Nehisi Coates’ Between the World and Me and Roxanne Gay’s Bad Feminist. By examining the authors against the standards of credibility as set by rhetoricians such as Erving Goffman and Aristotle, conclusions may be drawn about their efficacy. From that point, it may be derived how the ethos of the authors’ messages is affected by their use of rhetoric.